PLANNING STRATEGY FOR THE DEVELOPMENT OF LAKE MATANO TOURISM DESTINATIONS IN NUHA DISTRICT, EAST LUWU REGENCY - Dumais, Revin Ernest; Akib, Haedar; Ismail, Ismail (Jurnal Aktor, 2025)
This research aims to determine the planning strategy for developing the Lake Matano Tourism Destination in Nuha District, East Luwu Regency. This type of research is qualitative research using observation, interview and documentation data collection techniques. The data analysis technique uses Fishbone Analysis which is considered to make it easier for researchers to formulate planning strategies for developing the Lake Matano Tourism Destination in Nuha District, East Luwu Regency.The results of this research show that the planning for the development of the Lake Matano Tourism Destination in Nuha District, East Luwu Regency has several supporting factors in its implementation, namely the Development of Vision and Mission, where the development of this vision and mission must be in line with the agreed goals. Identification of opportunities and threats is the second factor by which the East Luwu Regency government can take advantage of opportunities and be able to overcome the threats it faces. In the third factor, the government must analyze the strengths and weaknesses of its surroundings. The fourth factor is formulating long-term goals. The long-term goal formulated by the East Luwu Regency government is the Grand Design Concept. Furthermore, the fifth factor is Generating Alternative Strategies, where the resulting strategy is the use of technology in terms of promotion. And the final factor is choosing a particular strategy to achieve the goal, the strategy used here is holding an annual event.